Londoners and Other Animals: Review of Hannah Velten, Beastly London: A History of Animals in the City - Kendall-Morwick, Karalyn (Humanimalia, 2014)
Hannah Velten, Beastly London: A History of Animals in the City. London: Reaktion Books, 2013. 288 pp. 50.00 (hb).